MEPANTIGAN PERFORMING ARTS: A REPRESENTATION OF BALINESE TRADITIONAL WRESTLING - I Wayan Gede Lamopia; Riza Wulandari (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2018)
Mepantigan performing arts is a representation of cultural elements that lead to art by displaying wrestling performances. The purpose of this research is to know the tradition of mepantigan represented by Roland Barthes's wrestling culture. The research method used is a case study by taking data collection techniques consisting of observation, interview and visual documentation. The results of this study indicate that In mepantigan, the myth which is formed from the previous society in 1930 and maintained steadily generation to generation, which is called as a tradition, has the potential to maintain regional tourism, especially in Batubulan, Gianyar, Bali. Barthes's concept of wrestling culture begins with the myth used in highlighting the identity formed by individuals, groups, or communities. Cultural wrestling is interpreted with the art of performances by displaying dance arts, theater that has a certain role according to Barthes which can be associated with the mepantigan Bali performance art. Therefore, the tradition of mepantigan can be used as a form of representation of Barthes’ wrestling culture.